A LINGUISTIC STYLISTIC EXPLORATION OF LEXICO-SYNTACTIC FEATURES IN SONYE TESS ONWUEME’S COLLECTION OF PLAYS - BOSSAN , Rita; MAIDAD, Deborah Sylvanus (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
This study examines a lexico-syntactic analysis of Osonye Tess Onwueme’s collection of plays: Lost in the Paradise, Broken Calabash, and Wazobia, aiming to explore the specific lexical and syntactic choices the playwright employs to communicate her thematic concerns regarding marriage, politics, and culture. Using a mixed-methods approach, the study is grounded in Halliday’s (1978) Social Semiotic Theory and Leech and Short’s (2007) Model of Stylistic Analysis. The findings reveal that Onwueme’s style is highly functional; she utilises a blend of simple and compound words, vivid descriptive language dominated by nouns and adjectives, and a dynamic range of sentence structures to create a distinct authorial voice. Her integration of borrowings from Nigerian languages serve to ground the plays in their cultural context and foreground her social critique. The study concludes that Onwueme’s linguistic choices are not merely aesthetic but are conscious, artistic acts that function as a form of advocacy to dismantle stereotypes, question authority, and champion the cause of the marginalised.